The effects of plan payment rates on the market for Medicare Advantage Dual‐Eligible Special Needs Plans. (20th May 2019) - McGarry, Brian E.; Layton, Timothy J.; Grabowski, David C.
Abstract: Objective: To determine the effect of higher potential benchmark payment rates on the market for Medicare Advantage (MA) Dual‐Eligible Special Needs Plans (D‐SNPs). Data Sources/Study Setting: Publicly available county‐level data from 2009 to 2015 regarding the number of D‐SNPs operating within the county, the enrollment in and five‐star quality of score of these plans, and the benchmark amounts used to determine capitated plan payments. Study Design: This study exploits the introduction of quality bonus payments to the MA program in 2012, and exogenous geographic variation in the potential size of these bonuses to estimate the effect of benchmark payment increases on the availability, quality, and take‐up of D‐SNPs. We use a difference‐in‐difference estimation approach to compare changes in the market for D‐SNPs in counties eligible for a double bonus to those that are not. Principal Findings: The doubling of bonuses was associated with a relative 29 percent increase in the number of D‐SNPs offered ( P = 0.021) and 0.1‐star increase in the average quality of available D‐SNPs ( P = 0.034). No relative increase in overall D‐SNP enrollment was detected. Conclusions: These findings indicate that larger benchmark payment amounts may influence insurers' decisions of whether to participate in the D‐SNP market but not dual‐eligibles' decision of whether to enroll in these plans. Future research is needed to inform discussions about whether D‐SNPs are a viable mechanism for integrating benefits for dual eligibles and the degree to which Medicare policies should support their continued growth.